The Effect of High Intensity Interval Training Applied with Vitamin E Reinforcement on Thyroid Hormone Metabolism - Akbulut, Taner; Cinar, Vedat; Erdogan, Ramazan (Lumen Publishing House, 2019)
The aim of the present research was to investigate the effect of vitamin E supplement applied with high intensity interval trainings (HIIT) on the thyroid hormone values. The research group consisted of 12 voluntary male sportsman; High intensity interval training and supplement groups (HIIT+V). HIIT group was participated only tabata model training program 3 days for 8 weeks. The HIIT+V group was taken the vitamin e in addition to the trainings. Blood samples were taken two times from the participants in the resting situation baseline and after the trainings session. Thyroid hormones were analyzed in the serum values taken from obtained the bloods of individuals. SPSS program was used in order to the data. Analysis results demonstrated that, There were no significant differences in comparison the groups (p>0,05). Within group analysis; T3, T4 and TSH was different in the HIIT+V group, while it found significant change only in TSH level in the HIIT group. Conclusion, it was found that the 8weeks of HIIT and Vitamin E reinforcement affect the thyroid hormones levels. It could said that interval trainings may lead to changes in thyroid hormones levels and may more effective when applied with vitamin E.
Keywords: Tabata; thyroid; vitamin E